A lot sizing problem in reverse for two items of different quality grades with an imperfect manufacturing process, time varying demand and return rates - Adetunji, Olufemi (University of Pretoria, 2022)
Dissertation (MEng (Industrial Engineering))--University of Pretoria, 2021.